2020
DOI: 10.1155/2020/8568153
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Numerical Research on V‐Cut Parameters and Auxiliary Cuthole Criterion in Tunnelling

Abstract: This paper aims at providing a sound theoretical solution to auxiliary central hole and the cutting parameters. For this purpose, the forming mechanism of V-cut cavity for cutting blasting was performed based on the hypothetical rock breaking mechanism of V-cut blasting. A theoretical solution for increasing the critical depth of the auxiliary center cuthole and the criteria for increasing the cuthole diameter of various types of cutholes when the rock attributes, explosive properties, and cuthole dip angle ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Tunnel excavation using V-cut blasting will result in a minimum burden increase as depth increases 22 . Each V's burden depends on the amount of explosive with which the blasthole diameter can be charged.…”
Section: Parallel Hole Cutmentioning
confidence: 99%
“…Tunnel excavation using V-cut blasting will result in a minimum burden increase as depth increases 22 . Each V's burden depends on the amount of explosive with which the blasthole diameter can be charged.…”
Section: Parallel Hole Cutmentioning
confidence: 99%
“…The advance rate per round tunnel excavation for parallel cut holes depends upon the size of the relief holes [6]. The auxiliary cut holes depend upon the drill length and drilling angle, only in the charging length < Drill length x cosθ [7]. Niches are pockets in the tunnel wall to reduce congestion and facilitate mucking.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Burden and Spacing are maintained between 0.7-0.8m ±1% deviations. The drilling pattern has been designed based on the 2007 edition of the NTNU model [7]. The penetration rate for Phyllite rock is considered 2.58m/min for the design of the blasting pattern and the specific charge required is adopted as 1.6kg/sm 3 .…”
Section: Tunnel Construction Cyclementioning
confidence: 99%
“…In addition to the above studies that have focused on traditional wedge cutting patterns, several recent studies have introduced a hole-outer delay into deep-hole wedge cutting blasting. For example, Shan et al 26 and Lou et al 27 proposed a modified mode of wedge cutting blasting with the delayed detonation of auxiliary vertical holes and reported that the delayed detonation of auxiliary vertical holes was beneficial for eliminating the residual rock mass in the bottom range to some extent. Through numerical simulation and theoretical derivation, Cheng et al 28 and Ding et al 29 described the rock breaking principle of double-wedge cutting blasting with hole-outer delay and subsequently verified the engineering applicability of this cutting pattern in deep-hole blasting driving.…”
Section: Introductionmentioning
confidence: 99%